2006
DOI: 10.1016/j.febslet.2006.04.059
|View full text |Cite
|
Sign up to set email alerts
|

The transmembrane domain provides nucleotide binding specificity to the bacterial conjugation protein TrwB

Abstract: In order to understand the functional significance of the transmembrane domain of TrwB, an integral membrane protein involved in bacterial conjugation, the protein was purified in the native, and also as a truncated soluble form (TrwBDN70). The intact protein (TrwB) binds preferentially purine over pyrimidine nucleotides, NTPs over NDPs, and ribo-over deoxyribonucleotides. In contrast, TrwBDN70 binds uniformly all tested nucleotides. The transmembrane domain has the general effect of making the nucleotide bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Instead, transporter components or conditions particular to the membrane environment missing in our analysis may be additionally important to functional assembly of TraD and possibly other T4CPs. In support of the latter hypothesis, the presence of the membrane-spanning domain altered interactions of native TrwB with some ligands in vitro (31). Moreover, Traxler and colleagues have shown that associations between F plasmid TraD monomers in vivo require N-terminal transmembrane sequences and that formation of stable, higher-order TraD oligomers in the inner membrane also appeared to involve other F proteins (28).…”
Section: Discussionmentioning
confidence: 59%
“…Instead, transporter components or conditions particular to the membrane environment missing in our analysis may be additionally important to functional assembly of TraD and possibly other T4CPs. In support of the latter hypothesis, the presence of the membrane-spanning domain altered interactions of native TrwB with some ligands in vitro (31). Moreover, Traxler and colleagues have shown that associations between F plasmid TraD monomers in vivo require N-terminal transmembrane sequences and that formation of stable, higher-order TraD oligomers in the inner membrane also appeared to involve other F proteins (28).…”
Section: Discussionmentioning
confidence: 59%
“…This result is consistent with the failure of D⌬2-134, Di⌬7-134, and G-D to exhibit conjugative dominance (Table 2 and data not shown). The importance of the Nterminal domains is further attested by previous studies showing that the N-terminally-truncated CP TrwB⌬N70 has altered stability and nucleotide-binding ability (23,24) and that both TrwB⌬N70 and N-terminally-truncated mutants of RP4 TraG exhibit monomeric behavior in vitro (22,47). The K6 and I59 mutants reveal that the N-terminal region of TraD is also important for assembly beyond the dimer stage: these mutants bound wild-type TraD and formed homodimers by cross-linking but did not form the larger cross-linked structures observed for TraD and TraDiN702 even when the F plasmid was present.…”
Section: Discussionmentioning
confidence: 97%
“…The biological relevance of these findings remains to be evaluated, but it should be noted that several studies have identified functions of the various T4CP domains that could contribute-directly or indirectly-to substrate binding. The NTDs, for example, are unlikely to directly bind substrates, but studies have identified several NTD functions, including binding interactions with other channel subunits, stimulatory effects on T4CP oligomerization and catalytic activity, and contributions to T4CP spatial positioning in the cell (17,(64)(65)(66)(67), that could indirectly affect substrate docking. By virtue of their possible accessibility to secretion substrates in the cytoplasm, the NBDs and CTDs might coordinate with the AAD to recruit substrates through direct substrate engagement.…”
Section: Discussionmentioning
confidence: 99%